2017
DOI: 10.1002/mawe.201700149
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the transferability of algorithms for the numerical optimization of cooling channel design in injection molding on metal gravity die casting

Abstract: The thermal mold design and the identification of a proper cooling channel design are primordial steps in the development of complex molds for injection molding. In order to find a suitable cooling channel system, a lot of effort is needed to avoid part warpage after solidification. In current research, a simulative procedure to optimize the cooling channel layout iteratively is being developed at the Institute of Plastics Processing. These algorithms are transferred to the metal gravity die casting process, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The accompanying simulations showed that cooling channels adapted to the heat distribution in the component can somewhat reduce the occurrence of thermal extremes in the component and mold. This is much less pronounced when considering the modules that can be used in reality, as could be seen in the first purely numerical considerations of idealized cooling channel layouts [7]. The small extent of the expected differences makes a comparison of the measured in-situ values (here the temperature) with the calculated ones poorly possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accompanying simulations showed that cooling channels adapted to the heat distribution in the component can somewhat reduce the occurrence of thermal extremes in the component and mold. This is much less pronounced when considering the modules that can be used in reality, as could be seen in the first purely numerical considerations of idealized cooling channel layouts [7]. The small extent of the expected differences makes a comparison of the measured in-situ values (here the temperature) with the calculated ones poorly possible.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the edges of the "U" are the hottest part in the mold and that in the casting the areas far away of the inlet are the coldest. Furthermore, during tool design in cooperation with the Institute of Plastics Processing (IKV) at RWTH Aachen University, the transferability of a developed algorithm for plastic injection molding for the optimization of the cooling channel layout for a more homogeneous solidification was considered [7]. This was done to test the transferability of the hypothesis that a homogeneously solidifying component produces less distortion, which was found to be true in plastic injection molding, to metal casting.…”
Section: Simulations and Optimized Cooling Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This in general represents a method with a highly inert reaction time with recent research focusing on optimizing the cooling channel design to improve heat dissipation at hotspot locations. 10 This study evaluates the potentials and possibilities of the application of heating conductor layers inside plasma sprayed coatings for permanent mold gravity die casting of an aluminum alloy. The specifications of a TiO 2 /Cr 2 O 3 heating conductor coating system described by Bobzin et al 11 are used in order to estimate the thermal surface power densities such a coating can realistically provide.…”
Section: Introductionmentioning
confidence: 99%